2001
DOI: 10.1348/000709901158433
|View full text |Cite
|
Sign up to set email alerts
|

The revised two‐factor Study Process Questionnaire: R‐SPQ‐2F

Abstract: The revision process has resulted in a simple questionnaire which teachers can use to evaluate their own teaching and the learning approaches of their students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

66
1,643
14
249

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,504 publications
(2,084 citation statements)
references
References 32 publications
(42 reference statements)
66
1,643
14
249
Order By: Relevance
“…Our path analysis models were consistent with published research, showing that students tended to adopt one approach or the other depending on the context in which they were learning [4,5,10,15] and that not only the context itself but also how it is perceived by students was influencing their approaches to learning [13,14]. With regards to the model proposed by J. Biggs [5], we found that the way students perceived their teachers seemed to have little or no influence on their learning approaches.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our path analysis models were consistent with published research, showing that students tended to adopt one approach or the other depending on the context in which they were learning [4,5,10,15] and that not only the context itself but also how it is perceived by students was influencing their approaches to learning [13,14]. With regards to the model proposed by J. Biggs [5], we found that the way students perceived their teachers seemed to have little or no influence on their learning approaches.…”
Section: Discussionsupporting
confidence: 88%
“…Learning approaches were measured with the Revised two-factor Study Process Questionnaire (R-SPQ-2F), developed by Biggs et al [4]. The original version consisted of 20 items scored from 1 ( this item is never or only rarely true for me ) to 5 (t his item is always or almost always true for me ), with 2 major subscales: the Deep Approach (DA) and the Surface Approach (SA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To thoroughly assess house officers’ ALM, the ALM questionnaire was developed which was a modification of the previous questionnaire, Revised Learning Process Questionnaire (R-LPQ-2F), established by Biggs and colleagues [14]. The R-LPQ-2F had been confirmed through confirmatory factor analysis consisting of eight factors with deep approaches to learning (goodness of fit indexes: CFI = 0.969 and SRMR = 0.027) including deep motivations and deep strategies, and surface approaches to learning (goodness of fit indexes: CFI = 0.965 and SRMR = 0.024) including surface motivations and surface strategies.…”
Section: Methodsmentioning
confidence: 99%